Analysis of the success of tuberculosis therapy - Muhammad Satrio Yuwono; Mustika Ratnaningsih Purbowati; Luhur Dewantoro; Ratna Wulan Febriyanti (Poltekkes Kemenkes Bandung, 2026)
Background: The success of tuberculosis (TB) therapy remains a major challenge in primary healthcare services, particularly due to low medication adherence and variations in support provided by Treatment Observers (PMO). These factors play an important role in determining treatment outcomes and achieving successful TB control programs. Objective: This study aimed to analyze the success of tuberculosis therapy and examine the relationship between medication adherence, PMO support, and treatment outcomes at Kembaran 1 Health Center. Methods: This study employed a quantitative cross-sectional approach and was conducted from December 2024 to January 2025. Data were collected using structured questionnaires administered to respondents. A total sampling technique was used, resulting in a sample of 52 tuberculosis patients. Data were analyzed using univariate and bivariate analyses. The Chi-Square test was applied to determine the association between medication adherence, PMO support, and tuberculosis therapy success. Results: Univariate analysis showed that 29 respondents (55.8%) had low medication adherence. Most respondents received support from PMOs (78.8%), while 21.2% reported inadequate support. Tuberculosis therapy was successful in 43 patients (82.7%), whereas treatment failure occurred in 9 patients (17.3%). Bivariate analysis demonstrated a significant association between medication adherence and tuberculosis therapy success (p = 0.013). In addition, PMO support was significantly associated with treatment success (p = 0.001). Conclusion: Medication adherence and PMO support were significantly associated with the success of tuberculosis therapy. Strengthening patient adherence and enhancing the role of treatment observers are essential strategies to improve treatment outcomes among tuberculosis patients in primary healthcare settings.